alpha-Tocopheryl succinate causes mitochondrial permeabilization by preferential formation of Bak channels - Procházka, Lubomír; Dong, Lan-Feng; Vališ, Karel; Freeman, Ruth; Ralph, Stephen J; Turanek, Jaroslav; Neužil, Jiří (Apoptosis, 2010)
Mitocans are drugs selectively killing cancer cells by destabilizing mitochondria and many induce apoptosis via generation of reactive oxygen species (ROS). However, the molecular events by which ROS production leads to apoptosis has not been clearly defined. In this study with the mitocan alpha-tocopheryl succinate (alpha-TOS) the role of the Bcl-2 family proteins in the mechanism of malignant cell apoptosis has been determined. Exposure of several different cancer cell lines to alpha-TOS increased expression of the Noxa protein, but none of the other proteins of the Bcl-2 family, an event that was independent of the cellular p53 status. alpha-TOS caused a profound conformational change in the pro-apoptotic protein, Bak, involving oligomerization in all cell types, and this also applied to the Bax protein, but only in non-small cell lung cancer cells. Immunoprecipitation studies indicated that alpha-TOS activates the two BH1-3 proteins, Bak or Bax, to form high molecular weight complexes in the mitochondria. RNAi knockdown revealed that Noxa and Bak are required for alpha-TOS-induced apoptosis, and the role of Bak was confirmed using Bak- and/or Bax-deficient cells. We conclude that the major events induced by alpha-TOS in cancer cells downstream of ROS production leading to mitochondrial apoptosis involve the Noxa-Bak axis. It is proposed that this represents a common mechanism for mitochondrial destabilization activated by a variety of mitocans that induce accumulation of ROS in the early phases of apoptosis.
Keywords: Tumor Suppressor Protein p53; Mitochondrial Membrane Transport Proteins; apoptóza; protein Bak; Jurkat buňky; Mitochondria; Apoptosis; lidé; Proto-Oncogene Proteins c-bcl-2; Antineoplastic Agents; protinádorové látky; protoonkogenní proteiny c-bcl-2; Reactive Oxygen Species; transportní proteiny mitochondriální membrány; mitochondriální membrány; mitochondrie; alfa-tokoferol; nádorový supresorový protein p53; reaktivní formy kyslíku; Mitochondrial Membranes; bcl-2 Homologous Antagonist-Killer Protein; Jurkat Cells; alpha-Tocopherol; Humans